2012
DOI: 10.1051/0004-6361/201218938
|View full text |Cite
|
Sign up to set email alerts
|

Radio perspectives on the Monoceros SNR G205.5+0.5

Abstract: Context. The Monoceros supernova remnant (SNR G205.5+0.5) is a large shell-type SNR located in the Rosette molecular complex and thought to be interacting with the Rosette Nebula. Aims. We aim to re-examine the radio spectral index and its spatial variation over the Monoceros SNR as well as study its properties of evolution within the complex interstellar medium. Methods. We extracted radio continuum data for the Monoceros complex region from the Effelsberg 21 cm and 11 cm surveys and the Urumqi 6 cm polarizat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Xiao & Zhu (2012) showed that the radio spectral index (α) of the remnant is about −0.41, derived from 21 cm, 11 cm, and 6 cm radio continuum data, which is generally consistent with the result of previous works (Dickel & Denoyer 1975;Graham et al 1982). Throughout this paper, all directions are described in Galactic coordinates to match the MWISP CO survey.…”
Section: Snr G2055+05 (Monoceros Nebula)supporting
confidence: 91%
See 2 more Smart Citations
“…Xiao & Zhu (2012) showed that the radio spectral index (α) of the remnant is about −0.41, derived from 21 cm, 11 cm, and 6 cm radio continuum data, which is generally consistent with the result of previous works (Dickel & Denoyer 1975;Graham et al 1982). Throughout this paper, all directions are described in Galactic coordinates to match the MWISP CO survey.…”
Section: Snr G2055+05 (Monoceros Nebula)supporting
confidence: 91%
“…Odegard (1986) suggested that the SNR is probably located behind the Rosette Nebula because of the absorption of the remnant's nonthermal emission by the southern H ii region Sh 2-275. Xiao & Zhu (2012) also suggested that the SNR is probably associated with the Rosette Nebula because of the identified western partial shell structures at ∼ 15 km s −1 using the new Arecibo HI 21 cm data. The remnant displays contrasting optical filamentary structures mainly on its northwestern, western, and southwestern edges.…”
Section: Snr G2055+05 (Monoceros Nebula)mentioning
confidence: 90%
See 1 more Smart Citation
“…The SNR and H ii region are thought to be interacting (Davies et al 1978;Smith 1973;Jaffe et al 1997;Fountain et al 1979;Gosachinskii & Khersonskii 1982). The polarization data presented by Xiao & Zhu (2012) do not cover the interface region between the two objects and show that the magnetic field in the Rosette Nebula is largely parallel to the Galactic plane. However, at a frequency of 5 GHz the observed polarization vectors are the result of either highly rotated background polarized synchrotron emission, considering the high RMs of about 500 rad m −2 measured in the nebula (Sect.…”
Section: The Rosette Nebula and The Mon Ob2 Molecular Cloudmentioning
confidence: 98%
“…Part of the northern Monoceros region has also been studied in polarization at radio frequencies by Xiao & Zhu (2012). These authors focused on the supernova remnant (SNR) Monoceros Loop, G205.7+0.1, north-west of the Rosette Nebula.…”
Section: The Rosette Nebula and The Mon Ob2 Molecular Cloudmentioning
confidence: 99%